Effect of Remote Ischemic Postconditioning on miRNA-145 and Troponin I levels in STEMI patients undergoing primary percutaneous coronary intervention - Pradita Diah Permatasari; Muhammad Fadil; Masrul Syafri (The Indonesian Heart Association, 2020)
Background: Primary Percutaneous Coronary Intervention Procedure (PPCI) results in reperfusion injury which will result in more extensive infarction. Remote Ischemic Postconditioning (RIPC) is a protective strategy to reduce the increase in the area of ​​infarction. miRNA-145 also plays a role in the protective effect of IPC and RIPC. Research Methods: This study uses a pre and post test approach only with control group design with experimental research designs. Data is taken at the Integrated Heart Services Installation RSUP Dr. M. Djamil Padang from July to November 2019, 40 patients with ST-segment elevation myocardial infarction (STEMI) performed RIPC. Bivariate analysis was performed to determine differences in levels of miRNA-145 and troponin I in STEMI patients underwent PPCI with and without RIPC using the Wilcoxon test and the Mann Whitney test. Results:A total of 40 patients who underwent the PPCI procedure were divided into two groups PPCI + RIPC (n = 20) and PPCI without RIPC (n = 20). There were no significant differences in the basic characteristics between the two groups. There were no significant difference in escalation of median expression of miRNA-145 in PPCI+ RIPC [pre test 36.33 (27.44-52.39), post test 34.83 (27.65-65.26), p = 0.765] compared to PPCI without RIPC [pre test 31.66 (26.31-43.28), post test 33.43 (26.83-64.97), p = 0.765]. There were an increase in median troponin I levels in both groups, PPCI+ RIPC [pretest 4,104.70 (67.30-40,000.00), post test 30,448.50 (120.00-16.3192.20), p = 0.001] and PPCI without RIPC [pretest 826.50 (17.00-48.259.00), post test 42.784.50 (2,119.00-162.897.00), p = <0.001]. Conclusion:There were no significant difference in median expression of miRNA-145 in STEMI patients before and after (48 hours) underwent PPCI+RIPC and PPCI without RIPC. There were a significant difference in median levels of troponin I in STEMI patients before and after (48 hours) underwent PPCI+RIPC and PPCI without RIPC. Keywords: Remote Ischemic Postconditioning, miRNA-145, troponin I